PENGARUH SELF LEADERSHIP, KERJASAMA TIM DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA BALI MANAGEMENT VILLA SEMINYAK - Novita Dewi; I Wayan Sujana; Ni Nyoman Ari Novarini (VALUES, 2021)
This research was conducted based on the different focus of discussion on selfleadership, teamwork and communication on employee performance. In addition, there is also a research problem regarding the decline in employee performance at Bali Management Villa Seminyak. This study aims to examine and analyze the effect of self- leadership, teamwork and communication on employee performance. This research wasconducted at Bali Management Villa Seminyak with a population and sample of 90 people. All data obtained from the questionnaire distribution is suitable for use, then analyzed using SPSS 25.0.The results of the study indicate that (1) self-leadership has a positive and significant effect on employee performance. (2) teamwork has a positive and significant effect on employee performance and (3) communication has a positive and significant effect on employee performance. The implication of this research is that self-leadership can be improved by paying attention to the positive indicators of patterns so that employee performance willincrease. Teamwork for mobilizing capabilities so that employee performance willincrease. Communication can be improved by paying attention to openness indicatorsso that employee performance can increase. Finally, employee performance can be increased by paying attention to indicators of quality, quantity, timeliness, effectiveness and independence.